Field notes contributed by Babs Padelford and Loren Padelford, spring 1987 - Padelford, Babset al; Padelford, Lorenet al (1987)
List of birds and locations contributed by Babs Padelford and Loren Padelford with observers Tanya Bray, W. Ross Silcock and B. J. Rose. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of spring 1987. Epson - sheet feed